The Extent of Depending on Handouts and other Learning Sources in University Education: An Empirical Study on Students in Sudanese Universities in Khartoum State - Mohamed A. Ismail; Ahmed B. Hasan (University of Science and Technology, Yemen, 2019)
The steady growth in higher education institutions and the number of students admitted in these institutions have affected the quality of higher education in Sudan. Students' dependence on handouts in academic achievement is one of the most important problems facing university education in Sudan. To achieve the study objectives, a field study on a sample of 600 students from Sudanese universities in Khartoum State was carried out in 2018 using a structured questionnaire characterized by both validity and reliability. The study results showed that most students rely on handouts as a primary source of academic achievement. The study also found that there are many problems related to using handouts, including lack of clarity in texts, pictures, and illustrations, and insufficient scientific materials. The study also identified the reasons for using handouts and reasons for the preparation of handouts by university teaching staff, as well as difficulties that limit the use of information resources in Sudanese universities. Based on these findings, the study presented a number of recommendations that, if adopted, would contribute to reducing reliance on handouts.